Atlas Vallard: A French narrative of America in the mid-sixteenth century - de Queiroz Pinto, Luciana (2023)
The Vallard Atlas is a double-sheeted atlas-book, with fifteen maps and nautical information sheets housed at the Huntington Library in San Marino, California. This atlas is rich in iconography, abundant in wind roses, and with a vast list of toponyms on the coast. On the first leaf, it bears the description “Nicolas Vallard de Dieppe, 1547”. Five maps describe territories in America, the subject of this essay. The objective of this article is to make a contextualized reading of the French perspective in the process of Iberian colonization in America.